BIOCHEMICAL STUDY ON THE HOST PLANT “ASAN” (TERMINALIA TOMENTOSA) LEAVES OF TASAR SILKWORM ANTHERAEA MYLITTA.D COLLECTED FROM ECO-POCKETS OF SIMILIPAL BIOSPHERE RESERVE, MAYURBHANJ, ODISHA - D. S. HOTA; G. C. PATRA; P. K. SATAPATHY; S. SATAPATHY (The Bioscan, 2014)
The Tropical tasar silkworm Antheraea mylitta Drury is an economically sericigenous insect abundantly cultivated around Simliplipal Biosphere area of Mayurbhanj district in Odisha. The larvae are reared on the Asan (Terminalia tomentosa) plant as the primary host plants. The leaves of T. tomentosa were procured from the ecopockets Thakurmunda, Kendujuani, Sarat, Jadida, Khadambeda and Kuliana of Similipal Biosphere Reserve. The concentration of protein, carbohydrate and ascorbic acid were analyzed. The analyses revealed that the leaves collected from Khadambeda showed highest concentration of protein (245.36mg/g) and ascorbic acid (1.89 mg/ g) whereas for the carbohydrate concentration in Kendujuani (4.63mg/g) are the suitable among all the ecopockets studied. However, the rearing performance is concerned may be due to high concentration of protein ERR (51.1%) at Khadambeda compare to other eco-pockets.